Tracking progress towards Kyoto and 2020 targets in Europe (Luxembourg, 2010)
"This report presents an overview of the progress achieved so far by the EU, its Member States and other EEA member countries towards their respective targets under the Kyoto Protocol and the EU burden-sharing agreement. The assessment is based on greenhouse gas emission data in Europe for 2008, the first year of the Kyoto Protocol's first commitment period which runs from 2008 to 2012. The recent availability of 2009 emissions estimates for the EU and a limited number of countries broadens, in these cases, the basis of the assessment to two years of the five-year commitment period."